43 Brief engagement and acceptance coaching in community and hospice settings (the BEACHeS Study): findings from the development and pilot-testing of a psychological intervention to enhance wellbeing at transition into palliative care. (13th October 2019) - Swash, Brooke; Gillanders, David; Finucane, Anne; Millington, Sue; Norwood, Sabrina; Spiller, Juliet; Strachan, Jenny; Kreft, Josh; Hulbert-Williams, Nick
Abstract : Diagnosis of terminal illness and subsequent transition into palliative care can cause fear and uncertainty, resulting in distress and decreased quality of life (Murray et al, 2007). Difficulty and distress when negotiating this transition can also be a barrier for patients and their families in engaging with the process of advanced or anticipatory care planning (Lund, Richardson & May, 2015). Acceptance and Commitment Therapy (ACT; Hayes, Strosahl & Wilson, 2011) is a promising but under-researched psychological intervention for supporting terminally-ill cancer patients (Arch & Mitchell, 2015). We developed and are pilot-testing a brief ACT-based intervention to improve quality of life and psychological acceptance for this group. A multiple baseline, single-case, non-controlled design is used. Ten participants have been recruited. Each receives five sessions with an ACT- trained facilitator, in the hospice setting. Quality of life, distress, and ACT-process changes are self-reported, weekly. Psychological flexibility and overall health are measured daily. The attrition rate is 60%. One participant demonstrated measurement floor and ceiling effects, but small increases in psychological acceptance. Two participants demonstrated small changes in quality of life and psychological flexibility, with some level of distress reduction. Finally, one participant shows tentative improvements in psychological flexibility, despite overall health remaining low. Participant interviews and three staff focus groups provided feedback on acceptability and feasibility. This study will complete in August 2019. Findings to date suggest that ACT may be beneficial for patients transitioning to palliative care, but high drop-out and measurement issues raise feasibility questions.